The Mental Health Consequences of Disaster-Related Loss: Findings from Primary Care One Year After the 9/11 Terrorist Attacks - Neria, Yuval (2008)
This study examines the long-term psychiatric consequences, pain interference in daily activities, work loss, and functional impairment associated with 9/11-related loss among low-income, minority primary care patients in New York City. A systematic sample of 929 adult patients completed a survey that included a sociodemographic questionnaire, the PTSD Checklist, the PRIME-MD Patient Health Questionnaire, and the Medical Outcomes Study Short Form-12 (SF-12). Approximately one-quarter of the sample reported knowing someone who was killed in the attacks of 9/11, and these patients were sociodemographically similar to the rest of the sample. Compared to patients who had not experienced 9/11-related loss, patients who experienced loss were roughly twice as likely (OR = 1.97, 95%; CI = 1.40, 2.77) to screen positive for at least one mental disorder, including major depressive disorder (MDD; 29.2%), generalized anxiety disorder (GAD; 19.4%), and posttraumatic stress disorder (PTSD; 17.1%). After controlling for pre-9/11 trauma, 9/11-related loss was significantly related to extreme pain interference, work loss, and functional impairment. The results suggest that disaster-related mental health care in this clinical population should emphasize evidence-based treatments for mood and anxiety disorders.